A promise of change: 52 Tuesdays (2013) – a case study of collaborative, low-budget feature-filmmaking practice - Dooley, Kath (Taylor & Francis, 2014)
52 Tuesdays (2013) is an ambitious and distinctively structured feature film that explores family relationships and one teenager's coming of age in contemporary suburban Australia. The story centers on 16-year-old Billie (Tilda Cobham-Hervey) who is surprised to discover that her beloved mother Jane (later known as James) wishes to transition from female to male. James needs some time out to adjust; however, mother and daughter vow to meet every Tuesday after school and spend the evening together, thus setting the ground rules for the structure around which 52 Tuesdays revolves. The film draws upon documentary elements in that it was in fact filmed over 52 consecutive Tuesdays and was therefore affected by significant change both on and off screen over the course of the year. Funded by the South Australian Film Corporation's now-defunct FilmLab program, 52 Tuesdays went into production based on a short treatment. This working document, which outlined characters and story arcs, changed during the yearlong production period as co-writers Matt Cormack and Sophie Hyde continued to develop the story on a weekly basis. In effect, this meant that the film's conception and development was closely linked with its execution, with the process of screenwriting not only driving production, but also being driven by production. In this article I examine the film's structure, the innovative practices of what I term ‘staggered’ screenwriting and production that bought the project to fruition, and consider the consequences of these working methods on the finished product. The article is informed by interviews with screenwriter Matt Cormack and director Sophie Hyde, as well as a formal textual analysis of the film. I argue that 52 Tuesdays' ‘one day a week’ style of filmmaking, with its open-endedness and incorporation of documentary elements, is one that fosters notions of authenticity for both its creators and audience. Furthermore, this timely, innovative and low-budget project has much intelligence to offer both practitioners and researchers investigating experimental approaches to feature film writing and development.